Studies on catalytic pyrolysis of empty fruit bunch (EFB) using Taguchi's L9 Orthogonal Array - Chan, Y.H. (Elsevier B.V., 2014)
This paper investigates the effects of four reaction parameters that include type of catalyst, catalyst loading, reaction temperature and nitrogen gas flowrate on the liquid (bio-oil) yield from the catalytic pyrolysis of Empty Fruit Bunch (EFB). The experimental design is based on Taguchi's L9 Orthogonal Array in which the reaction parameters are varied at three levels. The maximum liquid yield is predicted based on systematic experimental runs, and is found to be at 5 wt- of H-Y catalyst, 500-C and at nitrogen flowrate of 100 ml min-1. The predicted maximum liquid yield is validated with an experimental run at the corresponding predicted conditions. The bio-oil produced at the optimum reaction condition is characterized and compared with known bio-oil standards in the literature. Â© 2014 Energy Institute. Published by Elsevier Ltd. All rights reserved.